Assessing Nutritional Status and Functionality in Geriatric Population of Bangladesh: The Hidden Epidemic of Geriatric Malnutrition - Sompa Reza MS; Mohammad Rahanur Alam MSc; Akibul Islam Chowdhury MSc; Md. Abdullah Al Mamun MSc; Marufa Akhter MSc; Mohammad Asadul Habib MSc (Gerontology and Geriatric Medicine, 2023)
The average life expectancy of the Bangladeshi population has risen over the last decade due to economic growth and improved medical care. Although the increased number of older adults and their health is a significant concern, there is scarce of data regarding that. A community-based cross-sectional study was conducted to analyze the association between nutritional status and functional ability among selected Bangladeshi geriatric populations living in their homes. Of 400 participants, the prevalence of malnutrition, and people at risk of malnutrition was 25.4% and 58.8%, respectively. Furthermore, almost 80% of participants are dependent in terms of activities of daily living. High risk of falling ( OR  = 10.82; 95% CI: 5.85–20.37; p  ≤ .001), limited activities of daily living (IADL) ( OR  = 6.21; 95% CI: 4.02–9.58; p  ≤ .001), along with dependency in performing IADL ( OR  = 4.48; 95% CI: 2.83–7.06; p  ≤ .001) are significantly associated with malnutrition. Geriatric malnutrition can accelerate disability conditions, leading to early functional aging.